2012
DOI: 10.3724/sp.j.1263.2011.12293
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation in the elderly

Abstract: This review discusses atrial fibrillation according to the guidelines of Brazilian Society of Cardiac Arrhythmias and the Brazilian Cardiogeriatrics Guidelines. We stress the thromboembolic burden of atrial fibrillation and discuss how to prevent it as well as the best way to conduct cases of atrial fibrillatios in the elderly, reverting the arrhythmia to sinus rhythm, or the option of heart rate control. The new methods to treat atrial fibrillation, such as radiofrequency ablation, new oral direct thrombin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Sex steroid hormone-dependent mechanisms are evidenced by the effects of menopause on cardiovascular risk, 19 especially the increased risk of AF after menopause. 20 We sought to find the mechanical link between these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Sex steroid hormone-dependent mechanisms are evidenced by the effects of menopause on cardiovascular risk, 19 especially the increased risk of AF after menopause. 20 We sought to find the mechanical link between these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most common sustained arrhythmia reported in adult patients [1] and is associated with an at least a five-fold increase in the risk of stroke [2]. Vitamin K antagonists (VKAs) formed the cornerstone of thromboembolic prophylaxis in patients with AF for many years.…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is also a disease of the ageing population. In fact, it is the most prevalent chronic arrhythmia in patients aged 65 years (5.9% of the population), and its prevalence from 50 years old on, doubles every 10 years 2 . Approximately 40% of patients with cardiac amyloidosis have coexistent AF 3 .…”
Section: Introductionmentioning
confidence: 99%